Comprehensive multi‐tissue epigenome atlas in sheep: A resource for complex traits, domestication, and breeding - Deyin Zhang; Jiangbo Cheng; Xiaolong Li; Kai Huang; Lvfeng Yuan; Yuan Zhao; Dan Xu; Yukun Zhang; Liming Zhao; Xiaobin Yang; Zongwu Ma; Quanzhong Xu; et al. (iMeta)
Abstract Comprehensive functional genome annotation is crucial to elucidate the molecular mechanisms of agronomic traits in livestock, yet systematic functional annotation of the sheep genome is lacking. Here, we generated 92 transcriptomic and epigenomic data sets from nine major tissues, along with whole‐genome data from 2357 individuals across 29 breeds worldwide, and 4006 phenotypic data related to tail fat weight. We constructed the first multi‐tissue epigenome atlas in terms of functional elements, chromatin states, and their functions and explored the utility of the functional elements in interpreting phenotypic variation during sheep domestication and improvement. Particularly, we identified a total of 753,723 nonredundant functional elements, with over 60% being novel. We found tissue‐specific promoters and enhancers related to sensory abilities and immune response that were highly enriched in genomic regions influenced by domestication, while longissimus dorsi tissue‐specific active enhancers and tail fat tissue‐specific active promoters were highly enriched in genomic regions influenced by breeding and improvement. Notably, a variant, Chr13:51760995A>C, located in an enhancer region, was identified as a causal variant for tail fat deposition based on multi‐layered data sets. Overall, this research provides foundational resources and a successful case for future investigations of complex traits in sheep through the integration of multi‐omics data sets.